Ett drömspel: En lärarstudent utmanar gymnasieelever att tolka Strindberg - Katarina Rejman; Elisabeth Zetterholm (Dalarna university, 2021)
In this study, we follow a student teacher who has been given the assignment in her first school placement to work with August Strindberg's A Dream Play, in Year 2 of upper secondary school. The class she is teaching consists of 22 boys in the technology programme. Her challenge, as she herself expresses it, is how to get the pupils to experience A Dream Play as a meaningful text that concerns them and their lives. The theoretical frame of reference consists of theory of literature instruction, and a model of investigative-oriented literature instruction is used in the analysis to show how the teacher student carries out instruction and challenges the pupils to use different kinds of interpretative strategies. The results indicate that this instruction involves a number of features that characterise such literature teaching practice, for example, by giving pupils opportunities to connect their own experiences to Strindberg's play, and having them use their own interpretations and experiences to create a video. In this way, the instruction becomes situated in the classroom context and has an aesthetic and creative dimension. The pupils are also challenged to do a close reading of an excerpt and try out their interpretations in dialogue with their classmates.